Eastern Washington and Oregon in bloom : find and identify the 150 most common wildflowers - Kuhlmann, Ellen; Turner, Mark, 1954 April 8- (Timber Press, 2026)
"Eastern Washington and Oregon are home to a wide array of unique habitats, flourishing with unique plant life. Made for wildflower hunters and casual hikers alike, Timber Press's In Bloom series are portable and accessible-to-everyone guides to the most prominent wildflowers you are likely to see in a given region. Whether it be colorful, showy plants, or the bizarre and deadly, these and more are presented here in this easy-to-use field guide that features text and photographs of some of Eastern Washington and Oregon's more common and interesting wildflowers."-- provided by publisher.